Mapping Thriving at Work Research: An Integrative Systematic Review - Eliyana Eliyana; Titik Rosnani; Nur Afifah; Mustaruddin Mustaruddin (West Science Business and Management, 2026)
Thriving at work has become an increasingly important topic in organizational behavior and human resource management due to its role in promoting employee wellbeing, learning, and sustainable performance. This study aims to systematically review the development of thriving at work research across sectors and countries by identifying its dominant theoretical foundations, key antecedents, outcomes, and emerging research trends. A Systematic Literature Review approach was employed following the Preferred Reporting Items for Systematic Reviews and Meta Analyses guidelines. Fifty peer reviewed articles published between 2020 and 2025 were selected and analyzed. The findings reveal that thriving at work is primarily influenced by supportive leadership, job resources, organizational support, and psychological capital. Furthermore, thriving contributes positively to employee performance, innovation, work engagement, well-being, and career sustainability. The review also indicates that existing studies are dominated by quantitative and cross-sectional designs, with limited attention to longitudinal, cross cultural, and digital workplace contexts. This study contributes by providing an integrated understanding of thriving at work and highlighting future research directions in contemporary and technology driven work environments.